Quorum quenching potential of actinobacteria isolated from selected habitats in Peninsular Malaysia / Kavimalar Devaraj Naidu - Kavimalar Devaraj , Naidu (2017)
Quorum sensing (QS) is a cell-to-cell communication process that involves bacteria in a community regulating and coordinating various population density-dependent behaviours via signaling molecules commonly known as autoinducers. Currently, inhibition of QS is being targeted as a novel approach to curb bacterial pathogenicity. The discovery of anti-quorum sensing compounds has been crucial due to the tremendous increase of multidrug-resistant bacteria. In this study, Actinobacteria are targeted for their ability to attenuate quorum sensing as they are well known for their remarkable capabilities in producing a wide variety of secondary metabolites. A total of 207 actinobacterial isolates were screened for their ability to inhibit violacein synthesis in Chromobacterium violaceum CV026. Three actinobacterial isolates which are positive for violacein inhibition were then tested to determine their inhibitory activity against swarming and pyocyanin production by Pseudomonas aeruginosa PAO1. Based on the analysis of 16S rRNA gene sequences, these isolates belong to the genera Micromonospora, Rhodococcus and Streptomyces. Interestingly, this is the first report presenting anti-quorum sensing activity by a member of the genus Micromonospora. Pertaining to the findings of this study, members of the family Actinobacteria have a prospective ability in quenching QS signals.